A Facile Approach to the Synthesis of 3,4-Disubstituted-2-Aminothiazolium Derivatives through the Use of A “Volatilizable” Support - Li, Yangmei (2010)
A facile solid-phase synthetic approach to the synthesis of 3,4-disubstituted-2-aminothiazolium derivatives was reported. Functionalized aminomethylphenyl silica gel was used as a “volatilizable” support. The products were cleaved with 10% HF and were obtained in high yields and purities.